2016
DOI: 10.1161/circresaha.115.307679
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of a Novel Epsin–VEGFR2 Interaction Promotes VEGF-Mediated Angiogenesis

Abstract: Rationale We previously reported that VEGF-induced binding of VEGFR2 to epsins 1 and 2 triggers VEGFR2 degradation and attenuates VEGF signaling. The epsin ubiquitin interacting motif (UIM) was shown to be required for the interaction with VEGFR2, however the molecular determinants that govern how epsin specifically interacts with and regulates VEGFR2 were unknown. Objective The goals for the present study were (1) to identify critical molecular determinants that drive the specificity of the epsin and VEGFR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 54 publications
(86 reference statements)
1
49
0
Order By: Relevance
“…Interestingly, c-Cbl-dependent ubiquitination of epsin increases in response to VEGF stimulation to further promote the interaction between epsin and VEGFR2. The two residues identified as novel interfaces for binding to epsin 1, H891, and S1021 show potential in interacting with ubiquitin [48]. In this scenario, residues E183, E184, and E185 determine the classical function of UIM to bind with VEGFR2, while the novel ubiquitin-interacting-interface of the VEGFR2 kinase domain binds with ubiquitinated epsins to thereby reinforce interactions between the two.…”
Section: Modulation Of Vegfr2 But Not Other Signaling Pathways By Endmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, c-Cbl-dependent ubiquitination of epsin increases in response to VEGF stimulation to further promote the interaction between epsin and VEGFR2. The two residues identified as novel interfaces for binding to epsin 1, H891, and S1021 show potential in interacting with ubiquitin [48]. In this scenario, residues E183, E184, and E185 determine the classical function of UIM to bind with VEGFR2, while the novel ubiquitin-interacting-interface of the VEGFR2 kinase domain binds with ubiquitinated epsins to thereby reinforce interactions between the two.…”
Section: Modulation Of Vegfr2 But Not Other Signaling Pathways By Endmentioning
confidence: 99%
“…In this scenario, residues E183, E184, and E185 determine the classical function of UIM to bind with VEGFR2, while the novel ubiquitin-interacting-interface of the VEGFR2 kinase domain binds with ubiquitinated epsins to thereby reinforce interactions between the two. Remarkably, the study also demonstrates in vitro and in vivo activity of peptide-based angiogenesis modulators targeting this interaction [48]. …”
Section: Modulation Of Vegfr2 But Not Other Signaling Pathways By Endmentioning
confidence: 99%
“…Ubiquitin interacting motifs (UIMs) located at the downstream of ENTH domain in the N-terminal of the protein help to promote the interaction between epsin and VEGFR2, thus promoting endocytosis [25]. UIM is a 18-sequence motif that is able to specifically detect and bind to ubiquitylated VEGFR2 through specific residues on UIM and VEGFR2 respectively [26, 27]. After binding to the ubiquitylated VEGFR2, it acts as a type of cargo carrier, which promotes epsin binding [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…UIM is a 18-sequence motif that is able to specifically detect and bind to ubiquitylated VEGFR2 through specific residues on UIM and VEGFR2 respectively [26, 27]. After binding to the ubiquitylated VEGFR2, it acts as a type of cargo carrier, which promotes epsin binding [26, 27]. Epsin binds to the activated VEGFR2 and degrades it, which eventually causes VEGFR2 to break down into endosomes and lysosomes, leaving only parts of VEGFR2 remaining.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the complexity of the trafficking information packed in the cytosolic (and possibly transmembrane) portions of membrane proteins should not be underestimated. Important work done in the Chen lab clearly indicated that in mammalian epsins specificity determinants for the recognition of the receptor tyrosine kinase VEGFR2 are embedded within the UIM sequence environment(78)(79)(80). Further, it should be kept in mind that multi-spanning proteins like Ena1 usually contain additional/critical determinants in their intracellular loops; these regions may play a role in the recruitment of post-translational modifying enzymes; e.g., kinases, ubiquitin ligases/ARTs; or proteins that may assist in cargo recognition.…”
mentioning
confidence: 99%